Dial organic carbon fluctuations in a mangrove tidal creek in Sepetiba bay, Southeast Brazil - Rezende, C. E. (2007)
The carbon (C) concentration and flux, as dissolved organic carbon (DOC), particulate organic carbon (POC) and macrodetritus (MD), were quantified through 4 tidal cycles in a mangrove tidal creek in Southeastern Brazil. DOC was the major fraction of the total C concentration, accounting for 68 and 61% of the total C concentration during ebb and flood periods respectively. Concentrations of DOC (Ebb = 3,41 ± 0,57 mgC.L-1 and Flood = 3,55 ± 0,76 mgC.L-1) and POC (Ebb = 1,73 ± 0,99 mgC.L-1 and Flood = 1,28 ± 0,45 mgC.L-1) were relatively similar during the four tidal cycles. Macrodetritus presented a wide variation with concentration peaks probably related to external forces, such as winds, which enrich the ebb flow with leaf litter. DOC and POC fluxes depended primarily on tidal and net water fluxes, whereas MD fluxes were not. The magnitude of the DOC and POC fluxes varied with the area flooded at high tide, but not the MD fluxes. DOC was the major form of carbon export to Sepetiba Bay. During the four tidal cycles, the forest exported a total of 1,2 kg of organic carbon per ha, mostly as DOC (60%), followed by POC (22%) and MD (18%).